PENGARUH MANAJEMEN SARANA DAN PRASARANA TERHADAP MOTIVASI MENGAJAR GURU - wakhid, lutfi; Fahmi, Nurkafidz Nizam Fahmi; rahma dayanti, suci (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
ABSTRACT Facilities and infrastructure management is the administration of facilities and infrastructure which includes planning, organizing, implementing and evaluating activities in operational facilities and infrastructure programs in schools. And there is teacher teaching motivation, motivation is someone's encouragement to fulfill the responsibilities given to them. In this thesis we will examine the management of facilities and infrastructure at Minhajut Thullab Vocational School. The aim of this research is to determine the teaching motivation of teachers at Minhajut Thullab Vocational School, how much influence the management of facilities and infrastructure has on teacher teaching motivation at Minhajut Thullab Vocational School. This research uses quantitative descriptive methods with data collection techniques through questionnaires, observation, documentation. To test data validity and to find data reliability using the product moment formula, to find data reliability using Cornbach alpha. Then, to test the hypothesis, use the F test and T test, for the normality test, use the Kolmogorov-Smirnov formula. Data analysis uses simple linear regression analysis. Results of this research: (1). Management of infrastructure at Minhajut Thullab Vocational School is included in the poor category. (2). There is a significant influence between facilities and infrastructure on teacher teaching motivation as shown by the results of the t test with a t test beta coefficient value of 0.-621 which is negative, with a t count of 8.394 > 0.423 sig 0.05, then Ha is accepted and Ho is rejected. (3). Judging from the summary test, the R value or correlation coefficient is 0.621, while R square, the result of squaring the R value or coefficient of determination (KD) is 0.385, which means that the independent variable variable Y and 62% is influenced by other factors.